Gambaran Kebiasaan Sarapan Terhadap Konsentrasi Belajar Pada Mahasiswa SMA - Manungkalit, Maria; Sukmawati, Ermalynda; Hidayah, Nurul (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2021)
Breakfast is an intake of food that contains nutrients for the body that can have an important effect on concentration and health in everyone. Breakfast is one of the problems for students, especially breakfast. Regular food intake can affect a person's concentration in carrying out an action and learning, so that it can result in a person being able to produce the desired achievement. Learning is a learning process that must be carried out by each student. As a learning process requires action to determine the occurrence of students in the learning process. This study aims to determine the effect of breakfast habits with learning concentration on 122 vocational students in Surabaya. The research design used is descriptive research. Population and sample in conducting this research using total sampling. Instruments of breakfast habits and learning concentration using a questionnaire with a Likert scale approach. The results showed that 56.6% of students who had less breakfast habits could result in less concentration in studying, so that it could affect the learning process. The conclusion of this study is that students' good breakfast habits can affect students' learning concentration.